The historical geography of six major river basins in the north west of Western Australia since pastoral occupation - O'Grady, Colleen Margaid (Curtin University, 2004)
The thesis is based upon research into the historical geography of the pastoral industry in the six major drainage basins in the North West of Western Australia, in an attempt to outline its early development, and to explain how the rangeland degeneration associated with the Big Drought of 1936-1946 was exacerbated by unrealistic official expectations and poor management, particularly of stations in the hands of absentee corporate owners. it discusses the failure of government agencies to appreciate the effects of overstocking in an environment characterised by climatic variability and fragile rangeland resources. It draws attention to the official reluctance to take action against the destructive activities of profit-seeking corporate owners in the period leading up to and including the Big Drought, and of speculative leaseholders in more recent times The thesis attempts to differentiate between the grassmen as leaseholders bent upon generating a sustainable income from the rangeland through conservative management, and the exploitative owners and their (often) incompetent managers. It identifies the specific characteristics of each of the basins in terms of the physical environment, the process of pastoral occupation and the resulting changing patterns of land use. It examines the changing nature of the habitat, economy and society of the Aboriginal people, from the days prior to European penetration up to the late 20th century It also considers the future prospects of the pastoral industry in each basin, with references to such issues as environmental impact, Aboriginal land rights and occupance, and the mining industry. As well as a comprehensive overview of the historical geography of each river basin, the thesis also includes a study of infrastructural elements and bf the activities of all groups of people involved in the development of the river basins.